IDDF2020-ABS-0166 Novel mirna-based drug CD5–2 reduces liver tumour growth in diethylnitrosamine (DEN)-treated mice by normalising tumour vasculature and altering immune infiltrate. (18th November 2020) - Liu, Ken; Zhao, Yang; Chen, Jinbiao; Boland, Jade; Ting, Ka Ka; Gamble, Jennifer; McCaughan, Geoffrey
Abstract : Background: Hepatocellular carcinomas (HCC) exhibit abnormal (leaky) vasculature, hypoxia and an immunosuppressive microenvironment. The normalisation of tumour vasculature is an emerging approach to treat many cancers. Blockmir CD5-2 is an oligonucleotide-based inhibitor of the miR-27a interaction with VE-Cadherin, the endothelial specific cadherin. We previously showed CD5-2 normalises tumour vasculature by increasing VE-Cadherin expression (Zhao et al. Cancer Res. 2017). We studied the effect of CD5-2 combined with checkpoint inhibition on liver tumour growth, vasculature and immune infiltrate in the DEN-induced mouse model. Methods: DEN was given (25 mg/kg intraperitoneally) to male C57BL/6 mice at postnatal day 14. CD5-2 (30 mg/kg intravenously fortnightly) and/or anti-PD1 antibody (250µg intraperitoneally every 4 days) with their respective controls (4 groups) were given to the mice from age 7-months until harvest at age 9-months. Livers from treated and untreated mice were analysed. Results: We analysed human HCC data from The Cancer Genome Atlas and found high miR-27a and low VE-Cadherin were both associated with poorer survival (Log-Rank P =0.02 and P =0.01, respectively). In untreated mice, miR-27a expression was significantly increased in tumours compared to adjacent normal tissue (figure 1A ). Mice treated with CD5-2 + anti-PD1 antibody had significantly smaller tumours (50% reduction) compared to mice treated with either agent alone, controls, or untreated mice (figure 1B ). Histologically, tumours in the CD5-2 + anti-PD1 group exhibited a more favourable immune infiltrate (significantly higher CD3+ and CD8+ T-cells and lower Ly6G+ neutrophils) compared to tumours in other groups (figure 1C ). Tumours in CD5-2-treated mice had less leaky vasculature (as measured by Dextran beads extravasation) and less tumour hypoxia (carbonic anhydrase IX staining) compared to non-CD5-2-treated mice (figure 1D ). Conclusions: In the DEN model, CD5-2 normalised tumour vasculature and reduced tumour hypoxia. CD5-2 plus anti-PD1 antibody reduced tumour size possibly by altering immune infiltrate to being immunosupportive. The combination of vascular normalisation by targetting VE-Cadherin and immunotherapy is a promising novel approach to treat HCC.